ANALISA PENGARUH STRATEGI PEMASARAN TABUNGAN BRI BRITAMA PADA KEPUASAN NASABAH PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG SERUI - , Herman Depati, Prof. Dr. Basu Swastha Dharmmesta, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This Research has purpose to know: Knowing the effect of the savings bank BRI Marketing Strategy on Customer Satisfaction Britama PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Serui. Knowing the significant and the degree of influence of the variables that exist in the Marketing Strategy (Product, Price, Place / Distribution, and Promotion) on Customer Satisfaction PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Serui. Respondents of this study as many as 100 customers. This research is a case study and the data obtained by distributing questionnaires to the respondents. Testing the validity of using Confirmatory Factor Analysis and reliability testing using Cronbach Alpha. While the data analysis using Multiple Linear Regression analysis. Based on data analysis , the results of this research are: Simultaneously, the dimensions Product, Price, and Promotion a positive effect on customer satisfaction. That is, product strategy, pricing, and promotions have been accepted in the hearts of customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Serui. Semaikin good product strategy, pricing, and promotion of the greater customer satisfaction PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Serui. Partially, the dimensions of Place has no effect on Customer Satisfaction. This is due to customers of PT. Bank Rakyat Indonesia (Persero) Tbk. Branch Office of Serui has felt considerable satisfaction on product strategy, pricing, and promotion so that the place or location of the bank is not so considered by the customer.